Involvement of 5-HT1A receptors of the thalamic descending pathway in the analgesic effect of intramuscular heating-needle stimulation in a rat model of lumbar disc herniation - Ma, Yuhong; Zhan, Yijun; Pei, Jian; Ye, Gang; Chen, Yaoxin; Zhu, Wenyan; Shen, Haiyue (Frontiers in Neuroscience, 2023)
Background: Intramuscular (I.M.) heating-needle therapy, one of the non-painful thermal therapies, has been investigated to take effect of analgesia via the thalamic ventromedial (VM) nucleus by reducing the triggering threshold of descending inhibition alone, which could be modulated by intracephalic 5-hydroxytryptamine-1A(5-HT1A) receptors, other than the regular analgesia pathway. In this study, the effect and the potential serotoniergic mechanism of I.M. heating-needle stimulation at 43℃ in the pathological state of lumbar disc herniation (LDH) was explored.The modified classic LDH rat model of autologous nucleus pulposus implantation was utilized. I.M. inner heating needles were applied at the attachment point of skeletal muscle on both sides of L4 and L5 spinous processes. WAY-100635 and 8-OH-DAPT, 5-HT1A receptor antagonist and agonist, were separately injected into the bilateral thalamic mediodorsal (MD) and VM nucleus through the intrathalamic catheter. The nociception was assessed by bilateral paw withdrawal reflexes elicited by noxious mechanical and heat stimulation.Results: I.M. heating-needle stimulation at temperature of 43℃ for 30 and 45 min relieved both mechanical and heat hyperalgesia in LDH rat models significantly (P<0.05). Heat hyperalgesia was found enhanced significantly by the administration of WAY-100635 into the thalamic VM nucleus, blocking the effect of heating needle stimulation, in a dose-dependent manner (P<0.05), while no effects was detected after the injection into the thalamic MD nucleus (P>0.05). The injection of 8-OH-DAPT into the thalamic MD nucleus showed no modulating effects on neither mechanical nor heat hyperalgesia (P>0.05).I.M. heating-needle stimulation at 43 ℃ for 30 min could activate 5-HT1A mechanisms through the thalamic VM nucleus to attenuate hyperalgesia in LDH model rats. This innocuous thermal stimulation is speculated to selectively activate the descending inhibition mediated by the thalamic VM nucleus, taking effect of analgesia, without the involvement of descending facilitation of the thalamic MD nucleus.